Src Is a Prime Target Inhibited by Celtis choseniana Methanol Extract in Its Anti-Inflammatory Action. (14th March 2018) - Kim, Han Gyung; Choi, Subin; Lee, Jongsung; Hong, Yo Han; Jeong, Deok; Yoon, Keejung; Yoon, Deok Hyo; Sung, Gi-Ho; Lee, Seungihm; Hong, Suntaek; Yi, Young-Su; Kim, Jong-Hoon; et al.
Abstract : Celtis choseniana is the traditional plant used at Korea as a herbal medicine to ameliorate inflammatory responses. Although Celtis choseniana has been traditionally used as a herbal medicine at Korea, no systemic research has been conducted on its anti-inflammatory activity. Therefore, the present study explored an anti-inflammatory effect and its underlying molecular mechanism using Celtis choseniana methanol extract (Cc-ME) in macrophage-mediated inflammatory responses. In vitro anti-inflammatory activity of Cc-ME was evaluated using RAW264.7 cells and peritoneal macrophages stimulated by lipopolysaccharide (LPS), pam3CSK4 (Pam3), or poly(I:C). In vivo anti-inflammatory activity of Cc-ME was investigated using acute inflammatory disease mouse models, such as LPS-induced peritonitis and HCl/EtOH-induced gastritis. The molecular mechanism of Cc-ME-mediated anti-inflammatory activity was examined by Western blot analysis and immunoprecipitation using whole cell and nuclear fraction prepared from the LPS-stimulated RAW264.7 cells and HEK293 cells. Cc-ME inhibited NO production and mRNA expression of inducible nitric oxide synthase (iNOS), cyclooxygenase (COX-2), and tumor necrosis factor-alpha (TNF- α ) in the RAW264.7 cells and peritoneal macrophages induced by LPS, pam3, or poly(I:C) without cytotoxicity. High-performance liquid chromatography (HPLC) analysis showed that Cc-ME contained anti-inflammatory flavonoids quercetin, luteolin, and kaempferol. Among those, the content of luteolin, which showed an inhibitory effect on NO production, was highest. Cc-ME suppressed the NF- κ B signaling pathway by targeting Src and interrupting molecular interactions between Src and p85, its downstream kinase. Moreover, Cc-ME ameliorated the morphological finding of peritonitis and gastritis in the mouse disease models. Therefore, these results suggest that Cc-ME exerted in vitro and in vivo anti-inflammatory activity in LPS-stimulated macrophages and mouse models of acute inflammatory diseases. This anti-inflammatory activity of Cc-ME was dominantly mediated by targeting Src in NF- κ B signaling pathway during macrophage-mediated inflammatory responses.